Mapping the Progress in Natural Dye‐Sensitized Solar Cells: Materials, Parameters and Durability. Issue 23 (14th June 2022) - Alim, Md. Abdul; Repon, Md. Reazuddin; Islam, Tarikul; Mishfa, Kaniz Fatima; Jalil, Mohammad Abdul; Aljabri, Mahmood D.; Rahman, Mohammed M.
Abstract: The rapid growth of the population severely influences the supply of energy, accordingly ensuring clean energy has become a big challenge now and will be in the future. Fossil fuels have been satisfying the energy demand until now, but fossil fuels, being non‐renewable sources, will not be able to satisfy the energy demand in the future and will have a negative impact on the environment. Renewable energy sources have become the most demanding topic for researchers in this crisis. The solar cell, which is an abundant renewable energy resource, converts solar power into electrical energy without any environmental damage. Silicon solar cells have higher efficiency, but their high manufacturing cost, complicated procedures and environmental issues restrict their usage. Then dye‐sensitized solar cells (DSSCs) have been introduced as an alternative to silicon solar cells. In DSSC, both natural and synthetic dyes are used. Though synthetic dyes provide higher efficiency, they are environmentally harmful. Afterward, the concept of natural dye‐sensitized solar cells (NDSSC) have been materialized where only natural dyes are used. Researchers and environmentalists are looking for natural dyes as a replacement for synthetic dyes in recent times, as natural dyes are plentiful, can be collected naturally and have no environmental effects. Natural dyes in the form of anthocyanins, carotenoids, flavonoids, chlorophylls, tannins and betalains are extracted from various portions of plants that include leaves, roots, flowers, fruits, seeds, barks, etc. In this review, we investigate natural sources of dyes, natural sensitizers (dyes), shortcomings and remedies, improvements in efficiency and stability, developments, and commercialization. In addition, recent advances and the comparison of natural and synthetic dyes have been discussed in this review. Abstract : In this review, we investigate the natural sources of dyes, natural sensitizers (dyes), shortcomings and remedies, improvements in efficiency and stability, developments, commercialization, and recent advances as well as comparison between natural and synthetic dyes.